Exponential type distributions and a generalized functional calculus for generators of C_0-groups - Lozynska, V.Ya. (Carpathian Mathematical Publications, 2011)
The properties of a dual space to a space of entire functions of exponential type of many complex variables, that on the real subspace belongs to L_p(R^n) (1p<∞) are described. A functional calculus for generators of strongly continuous groups of bounded linear operators on an arbitrary Banach space in a Fourier-image of such dual space is constructed.